Faktor-faktor yang Mempengaruhi Perilaku Konsumen Terhadap Keputusan Pembelian Jasa Laundry Sepatu Coora Premium Care Grand Galaxy - Rafi Athallah Majid; Evi Selvi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the factors that influence consumer behavior towards purchasing decisions for Coora Premium Care Grand Galaxy shoe laundry services. This study uses a quantitative approach method. The population used in this study were consumers who had used the Coora Premium Care Grand Galaxy shoe laundry service. Samples were taken as many as 100 respondents. Data obtained by researchers through questionnaires distributed through google forms. The researcher used multiple linear regression analysis to analyze the data. The results of this study indicate that cultural, social, personal, and psychological variables have a significant effect on purchasing decisions simultaneously. Social and personal variables have no effect and are not significant on purchasing decisions partially. The result of the calculation of the coefficient of determination is 0.434. This shows that the cultural, social, personal, and psychological variables are able to explain the purchase decision by 43.4%. While the remaining 56.6% is explained by other factors not discussed in this study.